(untitled) (Journal of Kidney Cancer, 2026)
Osseous metaplasia is rarely reported in renal neoplasms and is predominantly associated with a favorable prognosis. Low-grade oncocytic tumor (LOT) represents a novel diagnostic classification of renal neoplasms that exhibit overlapping features of oncocytomas and chromophobe renal cell carcinoma. To the best of our knowledge, there are two definitive cases of low-grade oncocytic tumors with osseous metaplasia in the English literature. We present the third case of a 52-year-old female diagnosed with a low-grade oncocytic tumor exhibiting osseous metaplasia.